Hubungan Tingkat Pengetahuan Masyarakat Tentang Vaksin Covid-19 Terhadap Tingkat Kecemasan Vaksinasi Pada Masyarakat Di Desa Kaduengang - Mey Lys Ceryah Hutasoit; Oryza Intan Suri; Ernawilis Ernawilis; Ahmad Fahruroji (STIKes IMC Bintaro, 2023)
ABSTRACT Introduction: Vaccination of antigenic materials used to produce immunity to a disease. Vaccination is carried out to prevent or reduce the causes of certain infectious diseases such as hepatitis, polio, diphtheria and the new one at this time, namely COVID-19. The COVID- 19 vaccination aims to reduce the transmission of COVID-19, reduce the number of deaths and deaths by COVID-19, and the COVID-19 vaccination aims to create (herd immunity) or herd immunity in the community. Research purposes: Knowing the relationship between the level of public knowledge about the COVID-19 vaccine and the level of vaccination anxiety in the village of kaduengang. Correlative analytic Research method: with a cross sectional study approach (cross-cutting). The research design is cross-sectional. The data used is the chis-quare test. The sample in this study were 80 respondents. The results: of the study can beconcluded that the results of statistical tests using the chi square test obtained a value of = 0.002 < = 0.05, meaning Ha is accepted and H0 is rejected, meaning that there is a significant relationship between the level of public knowledge about the COVID-19 vaccine and the level of anxiety about the Covid-19 vaccination. 19 in the community in the village of kaduenga. The conclusion of the relationship between the level of public knowledge about the covid-19 vaccine and the level of anxiety of the covid-19 vaccination in the village of kaduengang. Suggestion: the results of this study can be used as library material and increase knowledge, insight as input in an effort to improve the quality of learning for the progress of students and readers about the relationship between the level of public knowledge about the covid-19 vaccine and the level of anxiety of the covid-19 vaccination